2009
DOI: 10.1088/0964-1726/18/9/095009
|View full text |Cite
|
Sign up to set email alerts
|

Finding NEMO (novel electromaterial muscle oscillator): a polypyrrole powered robotic fish with real-time wireless speed and directional control

Abstract: This paper presents the development of an autonomously powered and controlled robotic fish that incorporates an active flexural joint tail fin, activated through conducting polymer actuators based on polypyrrole (PPy). The novel electromaterial muscle oscillator (NEMO) tail fin assembly on the fish could be controlled wirelessly in real time by varying the frequency and duty cycle of the voltage signal supplied to the PPy bending-type actuators. Directional control was achieved by altering the duty cycle of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
60
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 30 publications
0
60
0
Order By: Relevance
“…Linear actuation in air of such PPy actuators under a 2 MPa applied stress was demonstrated, showing a considerable deterioration in actuation performance after a few cycles of actuation. In another study, Scotch tape and petroleum jelly were used for encapsulation of PPy tri-layer actuators operating in water [19]. It was found that the Scotch tape increased the stiffness of the actuators and resulted in a dramatic loss in tip displacement.…”
Section: Introductionmentioning
confidence: 99%
“…Linear actuation in air of such PPy actuators under a 2 MPa applied stress was demonstrated, showing a considerable deterioration in actuation performance after a few cycles of actuation. In another study, Scotch tape and petroleum jelly were used for encapsulation of PPy tri-layer actuators operating in water [19]. It was found that the Scotch tape increased the stiffness of the actuators and resulted in a dramatic loss in tip displacement.…”
Section: Introductionmentioning
confidence: 99%
“…1). As widely reported in the literature [3][4][5][6][7][8][9][10][11][12][13][14][15], if the conductivity of the contacts and the polymer is very good, there will be a small ohmic potential drop along the actuator length, and the charging rate will be high, which generate higher strains. The higher is the strain, the higher is the tip displacement of the actuators.…”
Section: Introductionmentioning
confidence: 99%
“…INTRODUCTION LECTROACTIVE conducting polymers have attracted the attention of many researchers since their discovery in mid 1970s. One reason for this interest is that the electroactive polymers are considered to be alternative to conventional actuator and sensor materials due to their small electrical energy consumption, light weight and compliant properties, biocompatibility, ability to operate in air and fluidic media, insensitivity to magnetic fields and simple fabrication [1][2][3]. When a small electrical potential or current is applied to the polymer actuators typified by PPy and appropriately engineered, this causes an electrochemical reaction for doping and undoping the polymer layer(s) [4][5].…”
mentioning
confidence: 99%
“…Consequently, electroactive polymers, as unconventional actuators, can be used for a wide range of engineering applications such as in the growing area of biomimetics. Of these applications, the PPy actuator is employed as a propulsor in a swimming device (robot fish) [1,2]. There is a growing interest on the use of the polymer actuators in many other bio-inspired applications, [6][7].…”
mentioning
confidence: 99%
See 1 more Smart Citation